2023
DOI: 10.3389/fpubh.2023.1201054
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models for predicting depression in Korean young employees

Abstract: BackgroundThe incidence of depression among employees has gradually risen. Previous studies have focused on predicting the risk of depression, but most studies were conducted using basic statistical methods. This study used machine learning algorithms to build models that detect and identify the important factors associated with depression in the workplace.MethodsA total of 503 employees completed an online survey that included questionnaires on general characteristics, physical health, job-related factors, ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
1
0
0
Order By: Relevance
“…Remarkably, the logistic regression model, a key focus of our study, exhibits comparable effectiveness when benchmarked against commonly used ML models. This finding aligns with broader research on depression, where logistic regression has consistently demonstrated either superior or comparable performance compared to alternative ML models ( 31–33 ). Our observation prompts consideration of two pivotal factors that contribute to this alignment.…”
Section: Discussionsupporting
confidence: 86%
“…Remarkably, the logistic regression model, a key focus of our study, exhibits comparable effectiveness when benchmarked against commonly used ML models. This finding aligns with broader research on depression, where logistic regression has consistently demonstrated either superior or comparable performance compared to alternative ML models ( 31–33 ). Our observation prompts consideration of two pivotal factors that contribute to this alignment.…”
Section: Discussionsupporting
confidence: 86%